AIAA SCITECH 2022 Forum 2022
DOI: 10.2514/6.2022-2152
|View full text |Cite
|
Sign up to set email alerts
|

Improving PIC-DSMC Simulations of Electrical Breakdown via Event Splitting

Abstract: A newly developed variable-weight DSMC collision scheme for inelastic collision events is applied to PIC-DSMC modelling of electrical breakdown in 1-dimensional helium and argon-filled gaps. Application of the collision scheme to various inelastic collisional and gas-surface interaction processes (electron-impact ionization, electronic excitation, secondary electron emission) is considered. The collision scheme is shown to improve the level of noise in the computed current density compared to the commonly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Another approach to improvement of modelling of low-probability processes was recently proposed, 19,20 dubbed "event splitting", in which the variable-weight particles are split proportionally to the probabilities of processes that can take place during a given collision. It was shown that use of event splitting for collisions and boundary conditions with secondary emission can noticeably reduce the noise in PIC-DSMC simulations compared to the use of standard sampling approaches to collision process modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to improvement of modelling of low-probability processes was recently proposed, 19,20 dubbed "event splitting", in which the variable-weight particles are split proportionally to the probabilities of processes that can take place during a given collision. It was shown that use of event splitting for collisions and boundary conditions with secondary emission can noticeably reduce the noise in PIC-DSMC simulations compared to the use of standard sampling approaches to collision process modelling.…”
Section: Introductionmentioning
confidence: 99%